Developing community-based engagement in Smart Cities: A design-computational thinking approach - Lee, Chien Sing *; Wong, Daniel K. (2017)
Smart Cities development has progressed rapidly with Internet of Things (IoT), ambient intelligence and increasingly, crowdsourcing. Engaging the community thus plays a key role in developing meaningful communal growth along with other stakeholders. This paper briefly presents a pilot study on developing computational perspectives for community-based engagement and innovations in Smart Cities for the young and thereafter, to explore possibilities of engaging seniors in self and community development, and the young and old in community-based engagement and possibly in the future, the development of viable values-based innovations in information systems.